Can Mn coordination compounds be good candidates for medical applications? - Kozieł, Sandra; Wojtala, Daria; Szmitka, Magdalena; Sawka, Jacek; Komarnicka, Urszula K. (Frontiers in Chemical Biology, 2024)
Metal complexes in the medical area, especially cancer treatment have attracted serious attention mainly because metals exhibit unique properties: redox activity, metal-ligand interaction, etc. Metal centres provide unique foci for varied biological modes of action that often but not exclusively involve redox or metal-ligand reactions. Metal complexes offer alternative and flexible coordination geometries, electron and proton transfer sites, inner and outer sphere reactivities, sites for redox-active, hemi-labile, and non-innocent ligands, and a variety of potentially controllable properties for exploitation in a therapeutic or biological context. The discovery of the first anticancer, the metal-based compound cisplatin in 1965 by Barnett Rosenberg was a historical outstanding breakthrough and led to a new area of metal-drug discovery. Some metal-based compounds have FDA approval for clinical use, while some undergo clinical trials for various medical therapies. This mini-review focuses on recent progress on Mn-based complexes with potential anticancer, antibacterial, and antifungal activities.